27 Countries, 23 Languages, and Communication Challenges in the European Union: A Comparison with ASEAN Economic Community - Hardini, Tri Indri; GrangÃƒÂ©, Philippe (TAWARIKH, 2017)
ABSTRACT: This study aims to determine the bilingualism that was predominant in Europe 150 year ago; how Europe, at a time when literacy was very low, could have so many people mastering two languages or more; nowadays, what makes most of the European citizens monolingual, while they enjoy wide education opportunities; how respective national languages emerged in Western Europe; the working languages in use at the EU (European Union) now, compared to ASEAN (Association of South East Asian Nations). In this study, the authors have adopted a historical approach. The data were gathered from various academic references and documentation, while the research itself uses qualitative data analysis. The results of this analysis show that most of the European do not speak anymore a regional language, but are also generally unable to master the national language of neighbouring countries, although they have learned it at school. It appears that many Europeans, especially if they live in large countries, are lazy to learn foreign languages because they consider it as useless in their professional and private everydays life. Besides, in perspective of the ASEAN Economic Community launching, English language as a lingua franca may cover the needs of political and administration staff, but does not guarantee understanding and friendship between the peoples that constitute ASEAN. Therefore, it is recommended that in each ASEAN member country, languages and cultures from fellow ASEAN countries should be taught in selected schools. KEY WORDS: European Union; Regional and National Languages; Language Contact; Language Status; ASEAN Economic Community.Â  About the Authors: Dr. Tri Indri Hardini is French Lecturer at the French EducationÂ Department and Vice Dean for Academic and Student Affairs, Faculty of Language and Literature Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154,Â West Java, Indonesia. Dr. Philippe GrangÃ© is Lecturer in Linguistics and Indonesian Director of the Asia-Pacific University Institute, Faculty of Literatures, Languages, Arts and Social Sciences, La Rochelle University, 1 Parvis Fernand Braudel,Â 17042 La Rochelle Cedex 1, France. Corresponding authors: tihardini@upi.edu and pgrange@univ-lr.frHow to cite this article? Hardini, Tri Indri & Philippe GrangÃ©. (2017). â27 Countries, 23 Languages, and Communication Challenges in the European Union: A Comparison with ASEAN Economic Communityâ in TAWARIKH: International Journal for Historical Studies, Vol.8(2) April, pp.163-178. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (February 4, 2017); Revised (March 11, 2017); and Published (April 28, 2017).